Electrostatic and steric stabilization of precipitated nanoscaled barium sulphate - Peukert, Wolfgang; Gradl, Johannes; Schwarzer, Hans-Christoph (2006 AIChE Spring National Meeting - 5th World Congress on Particle Technology, 2006)
Aggregation plays an important role in synthesizing nanoscaled particles e.g. by a precipitation process in a T-mixer. The possibility to stabilize barium sulphate suspensions electrostatically as well as sterically by adding different polymers is studied experimentally. The influence of the initial molar ration of Ba /SO " ions on the resulting particle size distribution is shown. To investigate the influence of the chemical composition and of the conformation of the polymer on the potential of stabilizing colloidal suspensions, which is coupled directly to their adsorption behaviour on the particle surface, three different polymers (PVA80 poly vinyl alcohol - 80%-hydrolyzed, PVA98 poly vinyl alcohol - 98%-hydrolyzed and Dapral GE202) are used as capping agents. In this study operating conditions are searched, where stabilizing by polymers is possible. However, polymers do not only influence the surface properties of the precipitated nanoparticles but reduce the turbulence of the flow field and consequently damp the mixing intensity. This is reflected in larger mean particle sizes of the precipitate.
Keywords: Aggregation; Barium sulphate; Electrostatic and steric stabilization; Polymer adsorption; Precipitation; Turbulence reduction